PERAN PENYULUH PERTANIAN LAPANGAN TERHADAP KINERJA KELOMPOK TANI DI KECAMATAN SUKAMAKMUR KABUPATEN ACEH BESAR - Teuku Adian Makmur Rizqullah; Elly Susanti; T. Makmur (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
This study aims to determine the role of agricultural extension workers on the performance of farmer groups in Sukamakmur District, Aceh Besar District. The variables in this study include the role of agricultural extension workers and the performance of farmer groups. In this study, the authors used the Spearman rank correlation test. The results showed that the perception of farmer group members on the role of the extension worker as a facilitator was included in the role category with a score of 63.9%. Based on the perception of members of the farmer group on the role of the extension worker as a motivator, it is included in the role category with a value of 66.7%. Based on the perception of members of the farmer group on the role of the instructor as an educator, it is in the role category with a value of 63.9%, and based on the perception of members of the farmer group on the role of the instructor as a communicator, it is in the category of playing with a value of 69.4%. The perception of farmer group members on the performance of farmer groups in Sukamakmur District, Aceh Besar District is in the good category with a percentage value of 69.4% and another 30.6% is stated to have poor performance. Based on the rank-spearman correlation test, the value of R = 0.738, this means that there is a strong relationship between the role of agricultural extension workers and the performance of farmer groups in Sukamakmur District, Aceh Besar Regency.